Experimental Study on High Temperature Properties of Carbon Fiber Sheets Strengthened Concrete Cylinders Using Geopolymer as Adhesive. (2016) - Zhang, Hai-yan; Hao, Xu; Fan, Wang
Abstract: Twenty plain concrete cylinders, including unconfined cylinders and confined cylinders with 1, 2 and 3 layers of carbon fiber sheets using geopolymer as adhesive, were tested in axial compression at ambient temperature and after exposure to elevated temperatures, to investigate the strengthening effect of carbon fiber sheet-geopolymer system. The failure modes, load-displacement curves, axial and hoop strains of confined cylinders were compared with that of unconfined cylinders. The failure modes of confined cylinders after exposure high temperature are similar with those of ones at room temperature. When temperature is up to 300°C, the compressive strength of confined cylinders is a little more than that of ones at room temperature, and the ratio of increase on compressive strength which is 106.4% is double as that of at room temperature. However, the ductility of confined cylinders decreases significantly after exposure elevated temperatures. From stress-strain curves, it can be found that there is no obvious degradation on mechanical property after exposure to high temperatures. It shows that carbon fiber sheet-geopolymer system has an excellent resistance to high temperatures.